(untitled) (Research, Society and Development, 2023)
The production of pork and its by-products is currently in growing demand, bringing high profitability to the national agribusiness sector. Brazil is the fourth largest producer and exporter of pork in the world. And for the maintenance and guarantee of this market, a good performance of the official inspection service, present in the slaughterhouses, carried out by official veterinarians who carry out control and inspection activities for the supply of safe and quality products for human consumption, is essential. In the state of Rondônia, inspection of products of animal origin in state slaughterhouses is carried out by the IDARON Agency. The scope of this work is to present an exploratory analysis regarding the occurrences and reasons for deviations of swine carcasses slaughtered in the state of Rondônia, in an establishment under the State Inspection System (SIE), from January 2019 to June 2021. It can be seen that the total average of convictions is lower (1.13%), a percentage different from those found in other states of the federation. Among the main suspected causes of alterations found in condemned carcasses, are those that presented: sexual odor (20%), contusion/fracture (19.24%), cryptorchidism (14.2%), emergency (14.2%), abscesses (13.5%), contamination (7.3%), dermatitis/skin lesions (5.8%), adherence to the peritoneum (3.1%), cachexia (1.2%), melanosis (0. 78%), purulent lymphadenitis (0.39%) and pneumonia (0.39%). Thus, it is noted that for the maintenance of public health, the activities carried out by the official inspection service are essential in order to guarantee the safety of food.